PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PBL TERINTEGRASI TPACK UNTUK MENGEMBANGKAN KETERAMPILAN ABAD 21 SISWA KELAS VI SEKOLAH DASAR - Jenal Nirwana; Ana Fitrotun Nisa; Tuti Purwoningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of a learning device based on Problem Based Learning (PBL) integrated with the Technological Pedagogical Content Knowledge (TPACK) framework in developing 21st-century skills among sixth-grade elementary students. The developed learning device consists of a Teaching Module, Student Worksheets (LKPD), and assessment tools for evaluating the four core 21st-century skills (critical thinking, creativity, collaboration, and communication). The research employed the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The implementation was carried out through a limited trial at SDN Lamajang 03 and a wider trial in four elementary schools within the Lamajang cluster, involving a total of 181 students. The effectiveness of the device was measured using N-Gain analysis based on students’ pre- and post-learning 21st-century skill scores. The findings indicate that the PBL–TPACK–based learning device is effective in enhancing students’ 21st-century skills. In the limited trial, the average 4C score increased from 2.34 to 3.77, categorized as moderate to high improvement. In the wider trial, the score increased from 2.84 to 3.87, categorized as high improvement. The integration of PBL and TPACK successfully created active, collaborative, and contextual learning experiences, contributing positively to student competence development in accordance with the Merdeka Curriculum. These results confirm that the PBL–TPACK–based learning device is both feasible and effective for use in elementary IPAS learning.